Pengaruh Undang-Undang Akuntan Publik terhadap Minat Mahasiswa Akuntansi sebagai Akuntan Publik (Studi Kasus IIB Darmajaya) - Reva Meiliana; Rieka Ramadhaniyah (President University Press, 2019)
The purpose of this research is to examine the effect of Public Accountant according to Undang-Undang number 5 year 2011 about the regulation of Public Accountant in Indonesia towards the interest of Accounting students to become Public Accountant. The objects of this study are Accounting Students have graduated in Auditing in IIB Darmajaya. Kuesionaer that can be used to study as many as 184 pieces or can be said to be a response rate of 62%. Furthermore, the primary data that has been collected is processed and analyzed by using descriptive statistical analysis. Testing hypotheses were tested by using linear regression. The results showed empirical evidence that the Public Accounting Law have affected the interest became public accountant.